Entero-insular axis in children with simple obesity - Jerzy Starzyk; Krystyna Sztefko; Przemysław J. Tomasik (Pediatric Endocrinology, Diabetes and Metabolism)
Introduction: The entero-insular axis plays an important role in generation ofsatiety signal. Thus, disturbances in this axis can influence the path to a simple obesity. The aim of the study was to assess the function of the hormonal part of the entero-insular axis in children with simple obesity. Material and methods: Group of 13 girls with the simple obesity was analyzed and the results were compared with results taken in the control group of 10 healthy girls. Each girl was examined for the oral glucose toleranceand standard meal tests. Blood was collected beforestimulation and after 15,30, 60 and 120 min. Concentrations of insulin, glucagon, pancreatic polypeptide, cholecystokinin, gastric inhibitory peptide (GIP) and glucagon-like peptide 1 (GLP-1) were determined with radioimmunoassay. Fasted and postprandial levels of the peptides as well as their integrated outputs were measured. Results: The results indicated that the disturbances in th entero-insular axis were limited to hyperinsulinaemia and changes in secretion of cholecystokinin (CCK) and GLP-1 in obese subjects. The integrated output of CCK in obese girls was significantly higher (p<0.001) than in control group but exclu-sively after the meal test. Mean values ofthe integrated output of GLP-1 in both tests were significantly higher in the control group than in the obese girls (oral glucose tolerance test- OGTT: p<0.001; meal: p<0.05). After OGTT and test meal, neither plasma concentrations of glucagon, pancreatic polypeptide nor GIP differed in the obese girl and control groups. Conclusions: Low postprandial level of GLP-1 in obese children seems to be responsible for excessive ingestion of food and a weaker inhibition of gastric emptying, both resulting in obesity.